VEHICLE PERFORMANCE EVALUATION OF LIGHT BUS BASED ON USER DRIVING NEEDS - MA JianJun; ZHAO LiHui; LI Tong; CHENG Kan; FENG JinZhi; ZHENG SongLin (Jixie qiangdu)
In order to evaluate the vehicle performance of a certain type of light bus,this paper establishes the vehicle performance evaluation system and investigates the user driving needs,user scores the performance according to the satisfaction of driving needs. Analytical hierarchy process,grey relational degree method,structure entropy weight method are proposed for determining the weights of the performance. Combining the weights with the user score,the result of vehicle performance evaluation is obtained. The evaluating results of the three methods are consistent. Compared with the other two methods,the structure entropy weight method pays most attention to the situation of the user driving needs. Thus,according to the result of the structure entropy weight method,the recommendations for improvement of light bus performance are proposed.